Proposta de gestão ambiental para o Instituto Federal de Educação, Ciência e Tecnologia do Piauí, campus Teresina Central - Brito, Jacqueline Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The environmental responsibility of the High Education Institutions (HEIs) starts from the inclusion of sustainability principles, among these ones, there is the environmental management of all the academic and administrative activities. For this purpose, it is needed attention to the social and ecological costs for what enters into the Campi (food, energy, water, materials) and what makes it a remnant form, effluents, and other wastes. Based on these issues, this study aims in general to realize an environmental diagnosis and to propose an action plan in environmental management to the Federal Institute of Piauí (IFPI), Campus Teresina Central. The diagnosis broached the following aspects: solid waste; wastewater; consumption of office supplies; water intake; energy and fuel; urban tree planting; and environmental perception. At the research it was used an explanatory and descriptive method, besides the phenomenological approach. In order to achieve the proposed objectives it was utilized the following methodological procedures: bibliographical documental survey and fieldwork. The diagnosis pointed that the Campus Teresina Central, in the period of the researches' realization, couched an institution that has no initiative towards the operation over sustainable basis, as the Campus is a large contributor of environmental impacts. Therefore it was formulated an environmental policy to the Campus under discussion, objectives and environmental goals were defined, and it was also proposed an action plan about environmental management. Facing these aspects, it is believed that this work consists in an important tool for the Campus Teresina Central as well as in others HEIs of the state, and at the decision-making process toward actions that seek for sustainability in higher education

A responsabilidade ambiental das Instituições de Ensino Superior (IES) parte da inclusão dos princípios de sustentabilidade, dentre eles, a gestão ambiental de todas as atividades acadêmicas e administrativas. Para tanto se faz necessária a atenção aos custos sociais e ecológicos do que entra nos Campi (alimentos, energia, água, materiais), e o que o deixa sob a forma de resíduos, efluentes e outros desperdícios. Com base nesses questionamentos, o presente estudo teve como objetivo geral realizar um diagnóstico ambiental e propor um Plano de Ação em Gestão Ambiental para o Instituto Federal do Piauí, Campus Teresina Central. O diagnóstico abordou os seguintes aspectos: resíduos sólidos; efluentes líquidos; consumo de materiais de escritório; consumo de água, energia e combustível; arborização urbana e percepção ambiental. Na pesquisa, foi empregado o método explicativo e descritivo, além da vertente fenomenológica. Para alcançar os objetivos propostos, foram utilizados os seguintes procedimentos metodológicos: levantamento bibliográfico, documental, e trabalho de campo. O diagnóstico mostrou que a situação do Campus Teresina Central, no período da realização da pesquisa, traduz uma instituição que não apresenta qualquer iniciativa rumo ao funcionamento sobre bases sustentáveis, haja vista que o campus é um importante causador de impactos ambientais. Deste modo, formulou-se uma política ambiental para o Campus em discussão, objetivos e metas ambientais foram definidos, e proposto um Plano de Ação em Gestão Ambiental. Diante de tudo isso, acredita-se que esse trabalho consiste em importante instrumento para o Campus Teresina Central e demais IES superior do Estado, na tomada de decisão rumo a ações que busquem a sustentabilidade na educação superior
Keywords: Environmental education; Instituto Federal de Educação, Ciência e Tecnologia do Piauí; Educação ambiental; Gestão ambiental; Resíduos; Percepção; Piaui